Basedow-Graves’ disease in a pediatric patient with Sticlker syndrome, a new endocrine finding to improve personalized treatment - Roberta Onesimo; Cristina De Rose; Clelia Cipolla; Silvia Della Casa; Chiara Leoni; Annabella Salerni; Daniela Ricci; Giuseppe Zampino (Italian Journal of Pediatrics, 2020)
Abstract Background Stickler syndrome is a connective tissue disorder with predominantly autosomal dominant inheritance, with ocular, auditory and joint involvement. Thyroid dysfunction was not described as part of alterations in Stickler syndrome and in particular, the association between Stickler’s syndrome and Graves’ disease has never been previously reported in literature. Moreover, the presence of Graves’ disease is uncommon in the pediatric age (especially in children younger than 6 years old). Case presentation We report the case of a 5-years old child affected by Stickler syndrome who received the diagnosis of Graves’s disease, in absence of suggestive symptoms, during health supervision. Conclusions This is the first evidence of thyroid dysfunction and autoimmune pattern for Sticker syndrome. Further clinical reports are expected before suggesting the implementation of new clinical skills for Stickler syndrome, but this paper may contribute to improve personalized management of this rare disorder.